Open and Distance Education in Australia, Europe and the Americas National Perspectives in a Digital Age (SpringerBriefs in Open and Distance Education,, 2018)
This book is open access under a CC BY 4.0 license. This book describes the history, structure and institutions of open and distance education in six countries: Australia, Brazil, Canada, Germany, the UK and the US. It discusses how open and distance education is evolving in a digital age to reflect the needs and circumstances of national higher education systems in these countries, and explores the similarities and differences between the ways in which they are organized and structured. It is the first book to make such comparisons and draw conclusions about the nature of open and distance education in the context of various national higher education systems. In a digital era with growing use of online education as well as open and distance education, this book is particularly useful for policy-makers and senior administrators who want to learn about organizing and expanding open and distance education provision. It is also a valuable reference for researchers, academics and students interested in understanding the different approaches to open and distance education.